PROBLEMS OF ELEMENTARY SCHOOL TEACHER AT UPT SD INPRES KASSI-KASSI IN LEARNING DURING THE COVID-19 PANDEMIC. - Rasyid, Sriyanti; admin, admin (Publikasi dan UKI Press UKI Toraja., 2022)
This study describes the problems faced by teachers and students in the learning process during the Covid-19 pandemic, and describes how to solve the problems faced by teachers and students in the online learning process during the Covid-19 pandemic. This type of research is descriptive qualitative, which was conducted in UPT SD Inpres Kassi-Kassi, Makassar. The data collection technique in this research is a study of literature or literature. The results are various problems faced by teachers in the online learning process during the Covid-19 pandemic. The problems faced by teachers are the limitations of teachers in controlling and assessing students in the online learning process, then the limitations of teachers in providing material that is easily understood by students. The problems faced by students are the lack of facilities that can support online learning such as students who do not have mobile phones, laptops, or computers and lack of adequate internet network access (quota), then there are students who are less active in learning and student boredom in the learning process. Teaching online, so students feel unmotivated and lazy in participating in online learning. Various problems faced by teachers and students by dealing with teachers must increase creativity and ability in mastering learning technology by looking for learning models that are suitable for learning conditions during the pandemic, and the government also takes part in overcoming learning problems. And teachers must be able to process online classes to the maximum.